FRI0673 Clinical remission in tocilizumab-using rheumatoid arthritis patients can be overestimated: a cross sectional study using ultrasound sonography. (15th June 2017) - Nakabo, S; Tsuji, Y; Inagaki, M; Tsuji, H; Nakajima, T; Hashimoto, M; Furu, M; Tanaka, M; Ito, H; Fujii, T; Fujii, Y; Mimori, T
Abstract : Background: Several clinical remission (CR) criteria of rheumatoid arthritis (RA) contain acute-phase reactants [C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR)] as their components. However, it is known that they can be underscored by the usage of tocilizumab (TCZ). This may cause overestimation of CR. On the other hand, ultrasound sonography (US) provides objective information independent of acute-phase reactants and assessment by physician and patient, and can detect synovitis in RA patients in CR, which is called sonographic residual synovitis (SRS). Objectives: To assess whether CR of TCZ-using RA patients are overestimated, by using US. Methods: We recruited 402 RA patients. Bilateral 2–5 MCP, wrist, ankle, and 2–5MTP joints were scanned by using the Aplio500 (TOSHIBA) with a 12 MHz transducer. Power Doppler (PD) images were obtained by Superb Micro-vascular Imaging (SMI). Gray scale (GS) and PD images were scored using a 0–3 semi-quantitative scale. Clinical information was obtained from the Kyoto University Rheumatoid Arthritis Management Alliance (KURAMA) database, which is based on the assessments by physicians who were blind to the US results. The patients were divided into 4 groups based on their treatment: tumor necrosis factor alpha inhibitors (TNFi), TCZ, abatacept (ABT), and non-biologic (non-Bio) users. Two patients treated by tofacitinib were excluded because the number was too small to analyze. The Boolean (BL)-based, Simplified Disease Activity Index (SDAI)-based, Clinical Disease Activity Index (CDAI)-based, and Disease Activity Score (DAS)28-ESR-based CR criteria were assessed using SRS. Results: A total of 400 RA patients were analyzed. The number of patients in each treatment group is shown in the Table. When the BL-based, SDAI-based, and DAS28-ESR-based CR criteria were used, SRS in TCZ group was significantly stronger than the other groups (Fig 1 –3). On the other hand, when CDAI-based CR criteria was used, the difference was not significant among 4 groups (Fig 4). In TCZ group, CRP and ESR were significantly lower than the other groups, although other clinical indicators were comparable (Table). Conclusions: US revealed that CR in TCZ-using can be overestimated by BL-based, SDAI-based, and DAS28-ESR-based CR criteria. For TCZ users, CDAI-based CR criteria is more reliable than the other criteria. Disclosure of Interest: None declared